A synthetic peptide based on large yellow croaker (Larimichthys crocea) IFNG1R protein sequence has potential antimicrobial activity against Pseudomonas plecoglossicida - Lin, Yijun; Yang, Shunzhe; Wang, Xiaohong; Xie, Ruiyao; Cheng, Jie; He, Tianliang; Chen, Xinhua; Zhang, Xiang-Yang (Frontiers in Marine Science, 2022)
The overuse of antibiotics leads to the emergence of bacterial resistance, which poses a serious threat to aquaculture. Antimicrobial peptides (AMPs) display excellent antimicrobial activity and are thought to be the most feasible replacements for antibiotics. The usage of AMPs as feed additives has great application prospects in aquaculture. In this study, large yellow croaker interferon-γ related gene (IFNG1R) was cloned, and a 17-amino acids (aa) short peptide named SKL17-2 was synthesized based on its protein sequence. The synthesized SKL17-2 peptide possessed a strong antimicrobial activity against Pseudomonas plecoglossicida, which could cause visceral white nodules disease (VWND) in cultured marine fish, with a minimum inhibitory concentration (MIC) of 2 μM. SKL17-2 peptide also showed weak antimicrobial activities against other tested bacteria, indicating its narrow-spectrum antimicrobial activity. This suggested that SKL17-2 peptide may not kill probiotics in intestinal flora when used as the feed additive. Furthermore, SKL17-2 had broad temperature and pH stability, low cytotoxicity, and negligible hemolysis, indicating its good biosafety and stability. Mechanistically, the synthesized SKL17-2 peptide can form α-helical structure in a membrane environment and destroy P. plecoglossicida through membrane disruption. Thus, our data showed that SKL17-2 peptide may represent a potential feed additive used for prevention and treatment of VWND.